A quantification of calcaneal lateral plantar process position with implications for bipedal locomotion in Australopithecus. Issue 123 (October 2018) - Boyle, Eve K.; McNutt, Ellison J.; Sasaki, Tomohiko; Suwa, Gen; Zipfel, Bernhard; DeSilva, Jeremy M.
Abstract: The evolution of bipedalism in the hominin lineage has shaped the posterior human calcaneus into a large, robust structure considered to be adaptive for dissipating peak compressive forces and energy during heel-strike. A unique anatomy thought to contribute to the human calcaneus and its function is the lateral plantar process (LPP). While it has long been known that humans possess a plantarly positioned LPP and apes possess a more dorsally positioned homologous structure, the relative position of the LPP and intraspecific variation of this structure have never been quantified. Here, we present a method for quantifying relative LPP position and find that, while variable, humans have a significantly more plantar position of the LPP than that found in the apes. Among extinct hominins, while the position of the LPP in Australopithecus afarensis falls within the human distribution, the LPP is more dorsally positioned in Australopithecus sediba and barely within the modern human range of variation. Results from a resampling procedure suggest that these differences can reflect either individual variation of a foot structure/function largely shared among Australopithecus species, or functionally distinct morphologies that reflect locomotor diversity in Plio-Pleistocene hominins. An implication of the latter possibility is that calcaneal changes adaptive for heel-striking bipedalism may have evolved independently in two different hominin lineages.